The class I phosphoinositide 3-kinases α and β control antiphospholipid antibodies-induced platelet activation - Terrisse, Anne-Dominique; Laurent, Pierre-Alexandre; Garcia, Cédric; Gratacap, Marie-Pierre; Vanhaesebroeck, Bart; Sié, Pierre; Payrastre, Bernard (Thrombosis and Haemostasis, 2016)
Antiphospholipid syndrome (APS) is an autoimmune disease characterised by the presence of antiphospholipid antibodies (aPL) associated with increased thrombotic risk and pregnancy morbidity. Although aPL are heterogeneous auto-antibodies, the major pathogenic target is the plasma protein β2-glycoprotein 1. The molecular mechanisms of platelet activation by aPL remain poorly understood. Here, we explored the role of the class IA phosphoinositide 3-kinase (PI3K) α and β isoforms in platelet activation by aPL. Compared to control IgG from healthy individuals, the IgG fraction isolated from patients with APS potentiates platelet aggregation induced by low dose of thrombin in vitro and increases platelet adhesion and thrombus growth on a collagen matrix under arterial shear rate through a mechanism involving glycoprotein Ib (GPIb) and Toll Like Receptor 2 (TLR-2). Using isoforms-selective pharmacological PI3K inhibitors and mice with megakaryocyte/platelet lineage-specific inactivation of class IA PI3K isoforms, we demonstrate a critical role of the PI3Kβ and PI3Kα isoforms in platelet activation induced by aPL. Our data show that aPL potentiate platelet activation through GPIbα and TLR-2 via a mechanism involving the class IA PI3Kα and β isoforms, which represent new potential therapeutic targets in the prevention or treatment of thrombotic events in patients with APS.
Keywords: Antiphospholipid antibodies; blood platelets; phosphoinositide 3-kinases; thrombosis